PENGARUH FAKTOR SOSIAL EKONOMI TERHADAP JUMLAH PENUMPANG DI BANDAR UDARA JENDERAL BESAR SOEDIRMAN PURBALINGGA: THE EFFECT OF SOCIO-ECONOMIC FACTORS ON PASSENGER VOLUME AT JENDERAL BESAR SOEDIRMAN AIRPORT PURBALINGGA - Fauzun Maulana Firdaus; Juanita Juanita; Iskahar Iskahar (Techno (Jurnal Fakultas Teknik, Universitas Muhammadiyah Purwokerto), 2026)
ABSTRACT The growth of passenger volume at JB Soedirman Airport is influenced by various socio-economic factors, including population size, Gross Regional Domestic Product (GRDP) per capita, the number of domestic tourists, trade facilities, and umrah agencies. This study aims to analyze the influence of socio-economic factors on the number of passengers at JB Soedirman Airport during the 20212023 period. A quantitative approach with a descriptive method was employed, focusing on the analysis of socio-economic factors affecting passenger volume using secondary data from the Central Statistics Agency (BPS) for 20212023. Multiple linear regression analysis was used to measure the relationship between passenger volume and five independent variables: population size, GRDP per capita, the number of domestic tourists, trade facilities, and the number of umrah agencies. The results of the study indicate that all independent variables, namely population (X₁), GRDP per capita (X₂), number of domestic tourists (X₃), number of trade facilities (X₄), and number of Umrah bureaus (X₅), have a significant effect on the number of passengers (Y) at JB Soedirman Airport. The multiple linear regression model obtained is: Y = -326.256 + 0.000465X₁ + 0.0000064X₂ + 0.000089X₃ + 0.069X₄ + 36.514X₅. This model has been tested using the t test, F test, and coefficient of determination. The test shows that all variables have a significant effect partially (Sig. < 0.05), while the F test shows a significant effect simultaneously (Sig. = 0.005). The coefficient of determination (R²) value of 0.811 indicates that the model is able to explain the variation in the number of passengers by 0.811, while it is explained by other factors outside the model. Keywords: Passenger Volume, JB Soedirman Airport, Socio-economic Factors, Multiple Linear Regression.